Exploring the Construction of Adulthood and Gender Identity Among Single Childfree People in Mexico and Japan - Mandujano Salazar, Yunuen Ysela (2019)
This article presents the analysis of personal narratives of Mexican and Japanese single and childfree cisgender heterosexual individuals to explore how people who do not comply with heteronormative gender roles related to marriage and parenthood build their gender identities as adults. It draws on in-depth interviews with 24 informants who were raised and lived in these two countries, amid hegemonic discourses on adulthood, masculinity and femininity that emphasize some form of heterosexual partnership and reproduction. It is found that, men interviewed from both countries were able to narratively defend their adulthood and gender identity through other attributes that are part of hegemonic masculinity. On the contrary, women had difficulties constructing themselves congruently; they recurred to external traits of hegemonic femininity to defend their womanhood, but to personality and lifestyle qualities related to hegemonic masculinity to construct their adulthood.